Strategi Sekolah dalam Membentuk Karakter Disiplin Peserta Didik di SDN 075047 Bakaru - Renata Jernih Putri Gea; Sergius Lay; Evimawati Harefa (Journal New Light, 2025)
This research was motivated by symptoms of student indiscipline who showed behavior that violated established school regulations. This situation must be paid attention to by schools through the formation of disciplinary character. The aim of this research was carried out by researchers to determine the school's strategy in forming the disciplined character of students. The research method used in this research uses qualitative research with a case study approach. Sample selection used purposive sampling technique. Data collection techniques were carried out using observation, interviews and documentation techniques. Data validity testing was carried out using triangulation, namely data source triangulation and technical triangulation. Researchers found the findings, namely the school's strategy in forming the disciplined character of students at SD Negeri 075047 Bakaru which includes guidance during morning roll call by the picket teacher, strengthening the class teacher, the role of religious teachers, pamphlet media, school rules, class rules and teachers being role models for discipline. applied to students with the aim of continually forming disciplinary character to provide good changes in disciplinary character for students. This is proven by showing that students have a disciplined character who obeys the existing regulations at SD Negeri 075047 Bakaru.